DETERMINANTS AND CHOICES OF OFF-FARM WORK AMONG RICE FARMERS IN A DEVELOPING COUNTRY - M. Rizwan; Z. Deyi; A. Nazir; R. Osati; L. Traore; G. R. Sargani (Journal of Animal and Plant Sciences, 2017)
The present study analyses the relative importance of off-farm activities and factors influencing off-farm activities among rice farmers in Punjab, Pakistan. The data from 400 farmers were collected in detail, from which 262 farmers were characterized with off-farm activities. Results revealed that self-employment was the most important off-farm participating activity amongst the rice farmers in categorized off-farm work. While, public service was the second important off-farm activity of the farmers. The results of multinomial probit regression indicated that education has significant impact and stimulate for engagement in each four categories of off-farm employment. Presence of younger population in households and land renting opportunity stimulate migration in other cities and countries. Less farming area, dependency ratio and large family size are the driving factors for participation in off-farm labour activities. There should be off-farm promoting activities within the region to enhance rice growing households’ income. Consequently, income will be helpful to mitigate the food security by investing in agricultural sector and also for improving the farmers’ living standard and poverty reduction as well.
Keywords: off-farm activities; migration; loan scheme; rice farmers; Pakistan